Development of haemophilic arthropathy of the ankle: results of a Delphi consensus survey on potential contributory factors. (24th November 2014) - McCarthy, A.; Moore, A.; Redhead, L.; McLaughlin, P.; Iorio, A.; Chowdary, P.
Summary The evidence base to support the prevention of haemophilic arthropathy remains incomplete. In particular there is a lack of evidence regarding the potential influence of non‐haematological factors. Additionally the ankle joint, the most affected joint in the primary prophylaxis era, has biochemical and structural features that should offer some protection from degeneration. Therefore, this study aimed to ascertain expert opinions on the potential contributory factors in order to inform a research agenda. The Delphi method, a group forum technique to achieve consensus of expert opinion was selected. It allows anonymous participation of a geographically disparate panel. A modified three‐round design was used with a multi‐professional international panel from 11 countries, 280 suggestions with the potential to influence arthropathy development were submitted in Round 1. These were analysed for theme, giving 47 factors in four categories: musculoskeletal intrinsic, extrinsic affecting physical health, compliance, education and non‐haematological management, and haemophilia related. Subsequently, consensus was ascertained on their importance for study. At survey completion, 31 panellists (86%) completed. 41 factors reached the pre‐selected level for consensus and 6 were rejected. The breadth of the factors put forward suggests that the panel believe pathogenesis of HA is multifactorial. Panel composition indicates results with high face and content validity capable of guiding future research. Developing an understanding of the relative influence of factors in each patient has the potential of not only individualizing replacement therapy with regard to frequency and trough levels but also individualizing other interventions that promote musculoskeletal health.